Response of terrace deposit thickness to climate change and tectonic deformation: An example of the Liyuan River in the Northeast Tibetan Plateau. (16th September 2021) - Wen, Zhenling; Chen, Dianbao; Guo, Lianyong; Pan, Baotian; Hu, Xiaofei; Li, Qiong; Ji, Xianghe; Yang, Jiaming
Abstract: The relationships between tectonics, climate and sedimentation are important for understanding landscape evolution. In order to elucidate these relationships, we conducted a detailed survey of the thickness of terrace deposits and the altitude of terrace surfaces along the Liyuan River valley, in the Northeast (NE) Tibetan Plateau. We have dated the formation ages of terraces T3 and T4 to 42 ± 3.2 and 93.7 ± 7.5 ka, respectively, using optically stimulated luminescence (OSL) method. By compiling the deposit thickness of terraces, palaeoclimate records and local tectonism, we found that variations in precipitation account for the temporal differences in thickness/rates of sediment deposition in terraces T4 and T3. However, the spatial distribution of terrace deposit thickness was determined by tectonism, including faulting and folding, which changed the local base level. In order to maintain a foreland‐ward‐dipping gradient, the Liyuan River adjusts its sedimentary processes via spatially differentiated aggradation.